Voluntary and compulsory integrated reporting: Evidence on reporting quality / Mira Susanti Amirrudin, Mazni Abdullah and Zakiah Saleh - Amirrudin, Mira Susanti; Abdullah, Mazni; Saleh, Zakiah (Universiti Teknologi MARA, 2021)
This study investigates the quality of Integrated Report (IR) in the voluntary and compulsory setting. This study's first objective is to measure IR disclosure quality and assess whether companies comply with the 2013 IR framework. The second objective is to examine whether there is any difference in reporting quality between the IR's compulsory regime and voluntary regime. A sample of 120 international companies listed on the International Integrated Reporting Council (IIRC) websites throughout three years (2014-2016) is selected based on the availability of all data for the analysis. A Total Integrated Reporting Disclosure Quality (TIRDQ) index is self-constructed through quantitative content analysis. The finding shows that the quality of IR improved from the year 2014 to 2016. There is no significant difference in the reporting quality between mandatory and voluntary IR. The findings have implications for policy setters who have mandated or are considering mandating IR.